Peningkatan Keterampilan Membaca Pemahaman Siswa dengan Menggunakan Model Pembelajaran Problem Based Learning Berbantuan Chromebook Kelas IV Sekolah Dasar Negeri 39 Kecamatan Pontianak Kota - Mauren Pinkan Grevinsca; Siti Halidjah; Asmayani Salimi (Journal on Education, 2024)
This research aims to describe the Problem Based Learning process and the results of improving students' reading comprehension skills with the help of Class IV Chromebooks at SD Negeri 39, Pontianak City District. The research method used is action research in the form of collaborative classroom action research. The research subjects were 31 students consisting of 9 men and 15 women as well as class IV A teachers at SD Negeri 39, Pontianak City District. The data collection technique used is observation of test questions. Data collection tools include observation sheets and tests. This research was conducted over two cycles. The results of this research include: The results of teacher activities using the Problem Based Learning model in cycle I had an average score of 67.33% in the good category, while in cycle II the average score was 85% in the very good category. The results of student activities using the Problem Based Learning model in cycle I had an average score of 60.66% in the quite good category, while in cycle 2 the average score was 84.66% in the very good category. As well as the results of assessing students' reading comprehension skills in cycle 1, the completion percentage value was 61.29% in the less able category and the average value was 70.16%, while in cycle II the completion percentage value was 87.09% in the capable category and the average value was 87.09%. the average was 83.87%, so the increase from cycle I to cycle II was 25.8%. Based on the results of research data and analysis, it shows that using the Problem Based Learning model can improve students' reading comprehension skills in class IV A of SD Negeri 39, Pontianak City District.